Pengembangan Kurikulum Aktual Yang Ideal (Dalam Membangun Mutu Lulusan MTs Zainul Hasan Genggong Probolinggo) - Anis Kurlillah; Ahmad Zaini Al Ma’rufi; Abu Sainullah; Tri Nur Fadilah; Badrus Soleh (HIBRUL ULAMA, 2025)
Curriculum development in Islamic junior high schools (madrasah) frequently encounters gaps between graduate competency demands, modern educational needs, and institutional religious identity. This issue is also identified in MTs Zainul Hasan (ZAHA) 1 Genggong, Probolinggo, an accredited “A” madrasah committed to maintaining high-quality graduate outcomes while preserving Islamic educational distinctiveness. This study aims to examine the actual curriculum development model that is considered ideal in strengthening graduate quality, with a specific emphasis on teacher competency reinforcement as the core determinant of educational output. The method employed is a descriptive qualitative approach using in-depth interviews and classroom learning observations. Research findings reveal that ZAHA 1 Genggong implements three dominant curriculum strengthening strategies: (1) academic qualification improvement through structured scholarship support for teachers’ continuing education, (2) continuous professional development via training workshops and teacher certification programs, and (3) periodic academic supervision to ensure instructional quality and compliance with learning standards. The research results highlight that the actual curriculum model applied integrates academic achievement, Islamic character internalization, and research-based learning innovation. This curriculum approach contributes to sustained graduate quality, alignment with 21st-century competencies, and improved teacher academic culture. The study concludes that an ideal actual curriculum in madrasah institutions must be adaptive, research-driven, and centered on continuous teacher capacity building to produce graduates who are competitive, highly competent, and rooted in Islamic values in accordance with the institutional vision.